Endophytes: A Treasure House of Bioactive Compounds of Medicinal Importance - Gouda, Sushanto; Das, Gitishree; Sen, Sandeep K.; Shin, Han-Seung; Patra, Jayanta Kumar (Frontiers in Microbiology, 2016)
Endophytes are an endosymbiotic group of microorganisms that colonize in plants and microbes that can be readily isolated from any microbial or plant growth medium. They act as reservoirs of novel bioactive secondary metabolites, such as alkaloids, phenolic acids, quinones, steroids, saponins, tannins, and terpenoids that serve as a potential candidate for antimicrobial, anti-insect, anticancer and many more properties. While plant sources are being extensively explored for new chemical entities for therapeutic purposes, endophytic microbes also constitute an important source for drug discovery. This review aims to comprehend the contribution and uses of endophytes as an impending source of drugs against various forms of diseases and other possible medicinal use.